Reliability and validity of the Japanese version of the overall dry skin score in older patients. Issue 1 (29th August 2021) - Konya, Issei; Iwata, Hiroaki; Hayashi, Miyuki; Akita, Tamami; Homma, Yoshie; Yoshida, Hideaki; Yano, Rika
Abstract: Background: Dry skin is the most common skin problem, especially in the elderly. However, there is no effective instrument to assess dry skin in Japan. This study aimed to evaluate the reliability and validity of the Japanese version of the overall dry skin score (ODS‐J), the gold standard for dry skin assessment. Materials and methods: A cross‐sectional study was conducted on 47 patients aged > 65 years. Images of skin on their limbs were captured using a digital camera; both upper and lower limbs were assessed ( n  = 4/patient). One dermatologist; two wound, ostomy, and continence nurses; and three nursing researchers independently evaluated the images using the ODS‐J to assess the intraclass correlation coefficient (ICC) for inter‐rater reliability. Stratum corneum hydration (SCH) and transepidermal water loss (TEWL) were the external criteria used to verify concurrent and known‐groups validity. Results: In total, 182 sites at which the SCH and TEWL could be measured were evaluated for the ODS‐J. The ICC for inter‐rater reliability of the six raters was 0.939 ( p  < 0.001). A higher ODS‐J was associated with lower SCH ( ρ  = −0.374; p  < 0.001) and lower TEWL ( ρ  = −0.287; p  < 0.001) values. The ODS‐J for the lower legs was significantly higher than that of the forearms ( p  < 0.001). Conclusions: The ODS‐J showed good inter‐rater reliability, concurrent validity, and known‐groups validity. It can be used by clinical nurses in Japan to observe patients' skin and is an effective indicator for the evaluation of skin care.